POLITIK HUKUM PEMBENTUKAN BADAN KEAMANAN LAUT DALAM MENJAGA KEAMANAN MARITIM DI INDONESIA - Muhammad Rafi Darajati; Muhammad Syafei (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2018)
As the largest archipelagic state in the world, Indonesia has a very wide sea area. Indonesia has a natural resources which are very plentiful. These are certainly advantageous position for Indonesia as the main strength both in the Southeast Asia and Asia Pacific if we capable to exploiting it. Those conditions also can be a boost for the whole layer components of the nation to increase the possessed capability to establish itself as a maritime nation. However the current maritime security in Indonesia still vulnerable due to high levels of violations there. It happens because there are certain parties who enter Indonesia wanting to exploit the national resources illegally. Based on the various problem that often occur, the effort to protect and ensure the security of the country by seas in an absolute must. Authors use juridical normative research method with literature studies. The result of this research shows that Indonesia government’s strong desire to bring Indonesia into a maritime nations which one of the issues is related to the maritime security is by establishing the Indonesia Coast Guard. As for the legal policy formation Indonesia Coast Guard is to synergy the various agencies in securing the Indonesia’s sea because there will not be a sectoral ego either in institutions or governments which is connected so the maritime security will be run effectively.